2005
DOI: 10.1159/000088172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effect of Vitamin E-Coated Dialyzer and Oral Vitamin E on Hemodialysis-Induced Cu/Zn-Superoxide Dismutase

Abstract: Background: We reported earlier that production of Cu/Zn-superoxide dismutase (SOD) increases markedly in hemodialysis patients but not in non-dialyzed chronic renal failure (CRF) patients. In this study, we compared the antioxidant effects of oral vitamin E supplementation (VE-PO) and vitamin E coating of a dialyzer (VE-BMD) by measuring increased Cu/Zn-SOD in hemodialysis patients. Methods: 31 hemodialysis patients were divided into two groups: 16 hemodialysis patients underwent usual dialysis with vitamin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…29,30 This condition has been demonstrated to contribute to the pathogenesis of various complications such as cardiovascular diseases, beta-2 microglobulinamyloidosis and protein malnutrition. To cope with this problem, dialyzers have been evolved into more biofriendly devices.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 This condition has been demonstrated to contribute to the pathogenesis of various complications such as cardiovascular diseases, beta-2 microglobulinamyloidosis and protein malnutrition. To cope with this problem, dialyzers have been evolved into more biofriendly devices.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated a possible benefit of vitamin E supplementation in cardiovascular risk reduction in patients with ESRD [39], and both vitamin E supplementation and the use of vitamin E-coated dialyzers have been shown to decrease oxidant stress in these patients [40]. However, vitamin E levels in predialysis patients with CKD have only been studied in a few previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we showed that the increase in plasma Cu/Zn-SOD levels is accompanied by enhanced expression of mRNA of Cu/Zn-SOD within leukocytes, demonstrating that the increased Cu/Zn-SOD level is not only due to the increased elimination insufficiency, but also due to the increase in its production [13]. Furthermore, we observed [15] that when lipid-soluble antioxidant vitamin E is orally given to hemodialysis patients, the plasma Cu/Zn-SOD level, used as an oxidative stress marker, was found to be reduced. Also, when a vitamin E-modified dialysis membrane was used, a similar decrease in plasma Cu/Zn-SOD level was observed, suggesting that the increase in plasma Cu/Zn-SOD was induced specifically by the hemodialysis process [15].…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, we observed [15] that when lipid-soluble antioxidant vitamin E is orally given to hemodialysis patients, the plasma Cu/Zn-SOD level, used as an oxidative stress marker, was found to be reduced. Also, when a vitamin E-modified dialysis membrane was used, a similar decrease in plasma Cu/Zn-SOD level was observed, suggesting that the increase in plasma Cu/Zn-SOD was induced specifically by the hemodialysis process [15]. …”
Section: Introductionmentioning
confidence: 99%